2022
DOI: 10.1242/jeb.244583
|View full text |Cite
|
Sign up to set email alerts
|

The acute phase response in bats (Carollia perspicillata) varies with time and dose of the immune challenge

Abstract: The acute phase response (APR) is a core component of the innate immune response and represents the first line of immune defense used in response to infections. Although several studies with vertebrates reported fever, decrease in food intake and body mass, as well as increase in neutrophil/lymphocyte ratio and total white blood cell count after lipopolysaccharide (LPS) inoculation, there was great variability in the magnitude of these responses. Some of these differences might reflect, to some extent, differe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 99 publications
4
8
0
Order By: Relevance
“…Moreover, LPS modulates other immunological functions such as bacterial killing ability of plasma, that represents the antimicrobial activity of humoral proteins of the innate immune system [42]. Recent reviews suggested that bats respond selectively to LPS administration, with species-specific differences in the activation of different components of this response [43,44]. Few studies have analyzed how APR is affected by changes in external factors directly related to global changes.…”
Section: Plos Onementioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, LPS modulates other immunological functions such as bacterial killing ability of plasma, that represents the antimicrobial activity of humoral proteins of the innate immune system [42]. Recent reviews suggested that bats respond selectively to LPS administration, with species-specific differences in the activation of different components of this response [43,44]. Few studies have analyzed how APR is affected by changes in external factors directly related to global changes.…”
Section: Plos Onementioning
confidence: 99%
“…In this way, we conducted 8 experimental trials on the climatic chamber with 8 individuals at a time, and the bats were assigned to only one thermal-feeding treatments. We decided to inject 10 mg LPS/kg in the nighttime because a recent work with C. perspicillata showed that higher doses of LPS in the activity period elicit a robust response in some components of the APR, such as reduced food intake and increased N/L ratio [44]. Selected ambient temperatures during the experiments were set close to the lower (27˚C) and upper limits (33˚C) of the thermoneutral zone of C. perspicillata (27-35˚C) [47].…”
Section: Plos Onementioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, LPS modulates other immunological functions such as bacterial killing ability of plasma (BKA), that represents the antimicrobial activity of humoral proteins of the innate immune system [41]. In bats, recent reviews suggested that bats respond selectively to LPS administration, with species-specific differences in the activation of different components of this response [42,43]. Few studies have analyzed how APR is affected by changes in external factors directly related to global changes.…”
Section: Introductionmentioning
confidence: 99%